Reunión Internacional: Intercambio de Experiencias y Estrategias Sobre Manejo Sostenible de la Amazonía, junto a la Unión Europea - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Reunión Internacional con representante de la Comisión Europea, sobre manejo sostenible de la Amazonía
ENGLISH: International meeting with representative of the European Commission on sustainable management of the Amazon region

SPANISH: Reunión Internacional con representante de la Comisión Europea, sobre manejo sostenible de la Amazonía
ENGLISH: International meeting with representative of the European Commission on sustainable management of the Amazon region
International Meeting: Exchange of Experiences and Strategies on Sustainable Management of the Amazon, with the European Union
Keywords: Social events|~|Iquitos (Perú)|~|Catholic Institutions|~|Catholic schools|~|Catholic priests|~|Acontecimientos sociales|~|Iquitos (Perú)|~|Instituciones Católicas|~|Escuelas Católicas|~|Sacedote Católica